Delivery of GalNAc-Conjugated Splice-Switching ASOs to Non-hepatic Cells through Ectopic Expression of Asialoglycoprotein Receptor - Juergen Scharner; Sabrina Qi; Frank Rigo; C. Frank Bennett; Adrian R. Krainer (Elsevier, 2019)
Splice-switching antisense oligonucleotides (ASOs) are promising therapeutic tools to target various genetic diseases, including cancer. However, in vivo delivery of ASOs to orthotopic tumors in cancer mouse models or to certain target tissues remains challenging. A viable solution already in use is receptor-mediated uptake of ASOs via tissue-specific receptors. For example, the asialoglycoprotein receptor (ASGP-R) is exclusively expressed in hepatocytes. Triantennary N-acetylgalactosamine (GalNAc) (GN3)-conjugated ASOs bind to the receptor and are efficiently internalized by endocytosis, enhancing ASO potency in the liver. Here we explore the use of GalNAc-mediated targeting to deliver therapeutic splice-switching ASOs to cancer cells that ectopically express ASGP-R, both in vitro and in tumor mouse models. We found that ectopic expression of the major isoform ASGP-R1 H1a is sufficient to promote uptake and increase GN3-ASO potency to various degrees in four of five tested cancer cells. We show that cell-type-specific glycosylation of the receptor does not affect its activity. In vivo, GN3-conjugated ASOs specifically target subcutaneous xenograft tumors that ectopically express ASGP-R1, and modulate splicing significantly more strongly than unconjugated ASOs. Our work shows that GN3-targeting is a useful tool for proof-of-principle studies in orthotopic cancer models, until endogenous receptors are identified and exploited for efficiently targeting cancer cells. Keywords: ASGR, asialoglycoprotein receptor, ASO, GalNAc, antisense oligonucleotide, splice switching, xenograft, receptor-mediated endocytosis, ASO delivery